PEMANFAATAN KONSEP SPACE WITHIN A SPACE DALAM PENGOLAHAN LAYOUT PADA INTERIOR - Ananda Trisiana; Ully Irma Maulina Hanafiah; Titihan Sarihati (Ide dan Dialog Desain Indonesia (Idealog), 2018)
Science ininteriordesignhas been widely used by the community to add value and provide solutions to problems in interior space. One of them is the number of designers applying the concept of open planto provide space design solutions to feel spacious, feel bright, and make it possible to carry out activities simultaneously. However, there are several activities that cannot be carried out simultaneously such as privacy spaces, namely bathrooms, meeting rooms etc. With these needs, the privacy area is usually placed outside the open plan area so that the use of open plan in the interior does not experience development in the processing of interior space. Even though there are four fundamental ways of connecting several spaces, one of them is space within a space. By adapting, developing, combining and using relationships between spaces within a space, the concept of open plan can create attractive spaces and can fulfill building functions. In this study the method used is descriptive analysis, that is, by describing and analyzing the concept of space within a space that has been applied by famous building architects and designers into interior layouts. The benefit of this research is to provide an alternative to processing interior space in the open plan concept in order to create a variety of designs. The purpose of this study is to provide a new perspective in processing concepts from an open plan by applying space within a space to separate space functions so that designers can provide privacy space in public areas, (or vice versa) without changing the essence of the open plan concept